On evidence: approach from the philosophical hermeneutics - Arturo García Rillo; Octavio Castillo y López; Jesús Hernández - Tinoco (ADIDE Federación, 2015)
In order to make the term analytical evidence to reveal the original meaning of its application to account for hermeneutical situations in the world of life, the study was conducted from philosophical hermeneutics stating the following: viewpoint, understanding horizon and fusion of horizons. In the viewpoint uses of evidence are described. The horizon of understanding traces the history of the concept of evidence highlighting the perspective of Husserl. In the fusion of horizons evidence described in three levels of reality: perceived (evidence from beliefs), known (evidence from knowledge) and constructed (deliberative evidence). We conclude that the historicity of the world allows rehabilitate the tradition and gives meaning to the evidence as the fact that it gets in the eyes through the original experience of hermeneutics situation that exists in practice.